Rainfall characteristics and erosion risk in the Brazilian semi-a, d tropical region - Chaves, Iêde de Brito; Freire, Octavio; Neto, Malaquias da Silva Amorim (Pesquisa Agropecuaria Brasileira, 2014)
The annual variability of the rainfall and the erosivity were evaluated for Catolé do Rocha, PB, Brazil. Although the data records correspond to only one location for a relatively short period, the analysis permits the following conclusions: 1. The annual rainfall is highly variable and its distribution is very irregular. 2. The highest daily rainfalls are more frequent in January, March and April. 3. More than 44% for the annual precipitation has Intensity higher than 20 mm/h. 4. The highest rainfall intensities for periods longer than 30 min were higher than in other brazilian tropical regions. 5. The critical period for erosion losses is January-March, because the soil is bare and is being prepared for planting.